2012
DOI: 10.1128/iai.00819-12
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Mycoplasma genitalium Infection of Human Endocervical Epithelial Cells Elicits Chronic Inflammatory Cytokine Secretion

Abstract: genitalium has yet to be defined, significant associations exist between M. genitalium and cervicitis, pelvic inflammatory disease (PID), and tubal infertility (23,25,30). Among female reproductive tract tissues, M. genitalium DNA has been detected in specimens from the vagina, endocervix, endometrium, and the fallopian tubes, suggesting that, after sexual transmission, the organism can disseminate from the lower to the upper tract. Similarly, outbred mice inoculated vaginally showed time-dependent ascension o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 31 publications
6
56
0
2
Order By: Relevance
“…The MG190 TaqMan PCR assay was described previously (30). In the current study, we evaluated performance of the MG191 assay with liquid cytology specimens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MG190 TaqMan PCR assay was described previously (30). In the current study, we evaluated performance of the MG191 assay with liquid cytology specimens.…”
Section: Resultsmentioning
confidence: 99%
“…Real-time PCR was performed using the CFX96 real-time PCR detection system (Bio-Rad Laboratories, Inc.) with twostep cycling parameters as described previously (30). Samples with a positive result using the MG190 TaqMan PCR assay were confirmed using a PCR assay targeting a conserved region of mgpB using primers 1F and 1R (16) with SYBR green detection chemistry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there are increasing numbers of studies suggesting that M. genitalium increases the risk of HIV-1 acquisition and/or transmission (2)(3)(4). Like other pathogenic mycoplasmas, M. genitalium is capable of causing chronic infections, as has been documented in cultured human endocervical epithelial cells (5), in animal models (6,7), in men with NGU (8,9), and in women with cervicitis (10). The mechanisms for persistence remain poorly understood.…”
mentioning
confidence: 99%
“…Furthermore, in vitro experiments demonstrated that adherent M. genitalium cultures decrease the integrity of endocervical cells, increasing the passage of HIV through epithelial barriers (31), which provides a molecular explanation for the increased risk of HIV acquisition in M. genitaliuminfected women (10,11). In vitro epithelial cell models revealed that M. genitalium infection induces host defense and inflammation pathways (32,33), as does a purified fragment of the immunogenic lipoprotein MG309 (34). A serine/threonine phosphatase (MG207) has been implicated in cytotoxicity to culture cells (35), and a peptide methionine sulfoxide reductase (MsrA) promotes survival in vivo in the lungs of hamsters (36).…”
mentioning
confidence: 99%